Caracterização dos efeitos celulares do Mono-N-butil-ftalato (MBP) mediados pela via estrogênica não-genômica ativada por GPER1 (GPR30) em células tumorais prostáticas humanas - Peixoto, André Rebelo [UNESP] (2016)
The mono-n-butyl phthalate (MBP) is the active metabolite of di-n-butyl phthalate (DBP), a plasticizer commonly used for industrial products, including medical devices, flexible plastics and cosmetics, has been described as an endocrine disruptor with estrogenic and anti-androgenic function, depending on the dose and the exposure period, particularly by interfering with the development of the male reproductive system. It is believed that some of the effects of endocrine disruptors are mediated by the non-classical estrogen G protein-coupled receptor - GPER1 (GPR30). In view of the worldwide problems regarding to degradation of plastics and their dispersion in the environment, and earlier evidences showed that phthalates have effects on the development and maturation of the prostate increasing the incidence of inflammatory and dysplastic lesions in rodents, this study aimed to evaluate the effect of MBP on androgen dependent prostate cancer cells (LNCaP) by modulating the activity of GPER1 (through its antagonist, G15). The LNCaP cells, maintained in RPMI culture, were expanded and treated in an incubator with 5% CO2 humid atmosphere at 37 ° C. The MBP dose to be used was 10 uM, selected from the following MTT cytotoxicity test (3- [4.5-dimethylthiazol-2yl] -2,5-diphenyl tetrazolina bromide). Thus were established the following treatment protocols: control: RPMI + 0.03% DMSO; MBP: 10 uM of MBP diluted in DMSO (0.03%) + RPMI; G15: 8 uM of G15 diluted in DMSO (0.03%) + RPMI; M+G: 8 uM of G15 + 10 uM of MBP (diluted in 0.03% DMSO) + RPMI. For the treatment of MBP together with G15 (M+G), the GPER1 antagonist was added to the medium 30 minutes prior to MBP. Cells were incubated under the described treatments at four different times: 15 minutes 45 minutes, 3 hours and 12 hours. After exposure, the cells were processed for RNA and protein extraction, techniques designed to Reaction Polymerase Chain Real Time After reverse transcription (RT-qPCR) and Western blotting, respectively. At all times it was evaluated the profile of protein expression for GPER1, pErk1 / Erk2, PI3K and pAKT to the overall assessment of the activation process of pathways mediated by GPER1. After this step, and showing a rapid effect of MBP in GPER1 activation, we selected the 12-hour time to assess possible late effects of treatment on genes and related proteins via the GPER1 and other key pathways in tumor progression process. Using the same treatment protocol was performed an transwell migration assay by plating 1x105 cells into translucent inserts were subsequently assessed by fluorescence microscopy for the quantification of the cells that passed through the pores. The transwell cell migration assay showed that treatment with MBP was able to increase the migration of LNCaP cells, whereas the other treatments were similar to control. Initial data showed that the MBP was able to increase the expression of GPER1, pERK-1/-2 after 45 minutes of exposure, but did not alter the expression of PI3K and pAKT. After 3 hours of exposure was an increase in the expression of GPER1 and pERK-1/-2 in the group treated with G15 antagonist for 12 hours and levels of these proteins were similar in all groups. These data lead us to believe that active GPER1 MBP to route in a short period of time preferably increasing the phosphorylation of ERK1-/-2. After the rapid activation of GPER1 by MBP and inhibition by G15 (45 minutes), it seems that establishes a period in which the cells had the pathway inhibited GPER1 (G15) and partially inhibited (M+G) and ceased to in this way phosphorylate ERK-1/-2 and AKT, considerably increases the expression of these phosphorylated proteins essential to activate cell survival pathways (3 hours). After 12 hours exposure, the expression of genes as GPER1, EGFR, AKT1, MAPK1 and MAPK3 is shown decreased in MBP group, which may indicate an attempt to rebalance the cellular levels of protein translated from those genes, which evidenced by western blot assays. Thus it is concluded that MBP, at the dose studied is able to activate the pathway of GPER1 for a short period of time, especially phosphorylating ERK-1/-2, including increasing the migration ability of these cells, which could, after over time, and multiple exposures, increase tumor progression; and that LNCaP cells are able, by cellular control mechanisms, to reduce the response to MBP over time in an attempt to restore the balance of cell survival pathways associated with GPER1.